Poetry and thought: a study of the major poetical works of Abraham Cowley - Fonge, Marinus Elateh (The University of Edinburgh, 2002)
The commendable revival of seventeenth century poetry at the start of the twentieth century neither generated sufficient scholarly interest in Abraham Cowley nor restored his ailing reputation. This is because the parochial tradition of viewing him as a rather minor Metaphysical, allied to the charge of obsession with topicality, have been compounded by his treatment as a transitional poet who harked back to the age of Donne and heralded that of Dryden. This summary judgement, though largely invalid as we intend to demonstrate, is reflected in critical opinion that has only very occasionally attempted to appreciate the diverse nature of Cowley's oeuvre. Motivation for this study therefore comes from the thoroughgoing need for a comprehensive study of the works of Cowley whose reputation was considered by his contemporaries to be as secure as that of any English poet before him. Our aim is to interpret his poetry by means of a closer reading than previously afforded in light of forces that shaped his thought and literary practice, discerning in the process how he left such a mark on his age and why this imprint remains indelible for us. The best way to effect a study on Cowley's works, as Jean Loiseau writing in French and to some extent David Trotter among his English critics have shown, is still to respect the divisions the poet himself made when grouping his poems in different blocks, thus encouraging a separate approach to each of them. But critical work on Cowley has mostly been confined to particular works or themes, Trotter's study for example restricted to the 1656 Poems, thereby ignoring the impact of the 1660 Restoration event of unsurpassable historical interest. Our study addresses this lacuna as it covers the gamut of Cowley's poetic career, including the key periods of civil war, the Interregnum, and the Restoration through to 1667 when he passed away. We reveal in the process the historical, political, and intellectual forces that condition his thought and thereby shape his poetry, bringing to the different sections propitious literary approaches to analyse the works in a manner as yet unattempted. Also, our chronological arrangement of material suitably reflects the evolution of thought and his development as a poet; plus, by respecting the formal divisions Cowley made we show how these help him resolve a life -long search for true poetic forms.